2019
DOI: 10.3389/fonc.2019.00452
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Expression and Association With Distant Disease-Free Survival in Triple Negative Breast Cancer: Analysis of 263 Patients Treated With Standard Therapy for Stage I-III Disease

Abstract: Background: We evaluated immunohistochemical AR expression and correlation with prognosis in a large series of homogeneously treated patients with primary TNBC. Material and Methods: Patients diagnosed with stage I-III TNBC between 2000 and 2015 at Istituto Oncologico Veneto who received treatment with surgery and neoadjuvant and/or adjuvant chemotherapy were included. Whole tissue slides were stained for AR. AR-positive expression was defined as >1% of positively stained tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 26 publications
2
37
0
1
Order By: Relevance
“…The current study is an exploratory step to develop a similar prognostic test for TNBC. Although AR has been explored as a prognostic marker in TNBC [4][5][6][7][8]10], these IHC based studies have shown inconsistent conclusions. Some of these studies have also found no association of AR with DMFS or overall survival (OS) [5,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The current study is an exploratory step to develop a similar prognostic test for TNBC. Although AR has been explored as a prognostic marker in TNBC [4][5][6][7][8]10], these IHC based studies have shown inconsistent conclusions. Some of these studies have also found no association of AR with DMFS or overall survival (OS) [5,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In some trials, patients with TNBC with AR expression had a better prognosis [12][13][14][15][16][17][18][19][20] ; however, others indicated that AR positivity was associated with poor prognosis. [21][22][23][24][25][26] In addition, in several studies, [27][28][29][30][31][32][33][34][35][36][37][38] it was illustrated that AR expression did not correlate with the prognosis of TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…39,40 In a previous meta-analysis, it was confirmed that AR positivity was associated with a lower risk of disease recurrence. 41 However, studies [12][13][14][15][21][22][23]27,28,32,[34][35][36][37][38] assessing the connection of AR expression and its prognostic value have recently been published, and have added to the inconsistent evidence. According to the Cochrane Handbook for Systematic Reviews of Interventions, 42 the meta-analysis should be updated every 2 years.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a multi-institutional study, AR-positive status was found to be a marker of good prognosis in US and Nigerian cohorts, a marker of poor prognosis in Norwegian, Irish, and Indian cohorts, and a neutral marker in the UK cohort [19]. In a trial that included 263 Italian patients who received standard treatment (NACT/adjuvant chemotherapy and surgery) for stage I-III triple-negative breast cancer (TNBC), it was found that 29.7% of patients were AR positive and that AR positivity was associated with worse outcomes, especially distant DFS [20]. However, in a study published in 2019, a retrospective pooled analysis, a total of 7,270 breast tumor mRNA profiles were evaluated for AR status, and AR positivity was related to good outcomes in the ER-positive/HER-2-negative group but with worse prog-nosis in the HER-2-positive group [21].…”
Section: Discussionmentioning
confidence: 99%